Redes sociales, funas, honor y libertad de expresión: análisis crítico de los estándares de la jurisprudencia de la Corte Suprema chilena - Contreras Vásquez, Pablo (2021)
This paper aims to fill the gap in Chilean literature and contribute to the systematization and critical analysis of the legal criteria and standards of how fundamental law norms have been applied on social networks publications cases. To this end, it reviews the jurisprudence of the Supreme Court in cases of acciones de protección during 2020 and sets the applicable criteria. In most cases, the Court has accepted the claims of those whose personal honor has been affected and has ordered the removal of the publications from the networks. The article adopts a critical look at the jurisprudence, since some decisions do not pay enough attention to the protection of freedom of expression, especially by following an excessively legalistic criterion. In addition, we argue that the acción de protección has procedural limitations to deal with the problems of doxing in social networks.